Ordered sets and complete lattices - A primer for computer science - Priestley, H (2002)
These notes deal with an interconnecting web of mathematical techniques all of which deserve a place in the armoury of the well-educated computer scientist. The objective is to present the ideas as a self-contained body of material, worthy of study in its own right, and at the same time to assist the learning of algebraic and coalgebraic methods, by giving prior familiarization with some of the mathematical background that arises there. Examples drawn from computer science are only hinted at: the presentation seeks to complement and not to preempt other contributions to these ACMMPC Proceedings.